STRATEGI PROMOSI WISATA DINAS KEBUDAYAAN, PARIWISATA, PEMUDA DAN OLAHRAGA KABUPATEN KUANTAN SINGINGI - Apriningsih, Lita; Sulistyani, Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study aims to find out the strategy of tourism promotion that has been implemented bythe Department of Culture, Tourism, Youth and Sports Kuantan Singingi Regency and todetermine the inhibiting factors of promotional activities undertaken. The research methodthat is used is qualitative descriptive. The main informants of the study were Head ofCulture, Tourism, Youth and Sport Office of Kuantan Singingi Regency, supportinginformants were head of Tourism and Creative Economy, Section Head of TourismResources, Tourism Section Head, and Staff of Tourism and Creative Economy. Datacollection is done by direct observation, interview, and documentation. Data analysis is donethrough the stages of data collection, data reduction, data presentation and conclusion. Theresults of this study concluded that the Tourism Promotion Strategy that has beenimplemented by the Office of Culture, Tourism, Youth and Sports Kuantan Singingi Regencyare advertising, sales promotion, public relations and online promotion. In addition,promoting inhibiting factors are the lack of budget funds provided by local government(Pemda), proposed proposals of activities often rejected by the government, often late inpreparing for all promotional purposes, and no special section of public relations that dealwith the issue of promotion. It causes the Department of Culture, Tourism, Youth and SportsKuantan Singingi difficult to conduct promotional activities.Keywords: promotion strategy, promotion mix, and torism